PENDIDIKAN KOMUNIKASI MASSA KEPADA MASYARAKAT - Nurharpani Nurharpani (Ensiklopedia of Journal, 2022)
Media institutions are internally grouped based on their technology type, such as print media institutions, film institutions, television institutions, and so on. Often these institutions are also grouped according to their respective types, for example local broadcasting press, national broadcasting press, and international broadcasting press. Or grouping local print media institutions, national print media institutions, or international print media institutions. To anticipate regional differences, it is not uncommon for media institutions to change the time excess and the time difference between one country and another. The internal grouping of media institutions is also grouped based on the characteristics of the writings and features they present on the mass media they produce. Different types of features and writings produced by the mass media are trying to be presented to readers, viewers, or listeners through the central activity in the production and distribution of knowledge of this media institution through information, ideas, and culture. This step is carried out in order to communicate the messages to be conveyed using a personal or group approach. The goal is to provide a response to the communicant to meet personal needs or group needs.